Consideraciones sobre las relaciones taxinómicas de Phymaturus patagonicus y Phymaturus palluma - Cei, José Miguel Alfredo María (1971)
Taxonomy, morphological characters and serological relationships of Phymaturus patagonicus and Phymaturus palluma are discussed. A true specific status of Phymaturus patagonicus may be supported by different kinds of evidence.